Terminology of mathematics: conventionality and correctness - Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2003)
The conventionality and correctness of the terminology of mathematics in textbooks are disscused. The concepts of the solution of equation, of the graph of a function, of the elementary event and other are analyzed.